Insights into Pamfil Şeicaru’s Pamphletary Discourse - Fănel Teodoraşcu (Styles of Communication, 2012)
The model of the pamphlet written by Pamfil Şeicaru is unique within the Romanian publicist writing because his discursive strategy of swearing does not make use of the offensive register of gross language and does not become a means of the sub-intellect rude embodiment. Şeicaru used to carefully choose his targets, his attention being mainly focused on those whom he considered to be the roots of the greatest evil and who, just like cancer, might have affected the whole society. Most of his pamphlets were written following the model of an indictment. In order to prove his targets’ guilt, Şeicaru made use of judicial norms, documents, facts, circumstances or depositions. Şeicaru’s campaigns could last for several years, preserving the destructive force even after the target’s death.